A meta-analysis reveals mostly neutral influence of scattered trees on pasture yield along with some contrasted effects depending on functional groups and rainfall conditions - Rivest, David; Paquette, Alain; Moreno, Gerardo; Messier, Christian (Agriculture, Ecosystems & Environment, 2013)
Scattered trees occurring throughout farmland matrix are prominent features of many human-dominated landscapes around the world, especially in livestock grazing systems. They are keystone structures that may play important roles in maintaining ecosystem functions, services, and farmland biodiversity. However, scattered trees in agricultural landscapes are declining worldwide due to intensive land use. They are often perceived by farmers as having negative impacts on agricultural production. Large-scale assessments in different biomes of agricultural yield in scattered tree ecosystems remain rare. Filling this knowledge gap may help improve decision-making regarding the value of scattered trees in agricultural landscapes. Using meta-analysis, we found that, across four tree functional groups (deciduous, Eucalyptus, N2-fixing, evergreen oak), mature scattered trees do not compromise pasture yield. The sign and magnitude of scattered tree effects on pasture yield did vary, however, among tree functional groups and according to precipitation levels. Our study suggests that, as drought pressure increases abiotic stress, tree facilitation by N2-fixing trees, and competition by Eucalyptus, will become the more common interactions between scattered trees and pasture. Management options exist to conserve and restore scattered trees in agricultural landscapes, but new policies are required to support their widespread adoption by farmers.
Keywords: Abiotic stress; Agroforestry; competition; Facilitation; Tree functional groups; tree-pasture interaction

Non-invasive tools to estimate stress-induced changes in photosynthetic performance in plants inhabiting Mediterranean areas - Guidi, Lucia; Calatayud, Angeles (Environmental and Experimental Botany, 2013)
In Mediterranean areas, plants are concomitantly exposed to various abiotic stresses such as light intensity, water deficit, extremes in air temperature, air pollutants, etc. These environmental pressures adversely affect plant development. Changes in photosystem activity are an early response of plants to abiotic stresses. Therefore, chlorophyll (Chl) fluorescence and gas exchange, two non-invasive, rapid and inexpensive techniques for measuring photosynthesis in leaves, have been widely used by plant ecophysiologists to analyse plant responses to stressful conditions. Chl a fluorescence and gas exchange parameters can be indeed used to evaluate changes in photochemical and non-photochemical processes in photosystems associated with electron transport, CO2 fixation, and heat dissipation. In this review, we focus our analysis on the effects of different abiotic stresses on the photochemistry of Mediterranean plants using Chl a fluorescence and gas exchange measurements. Since changes in photosynthetic parameters are observed in the absence of visual injuries, these methodologies constitute fundamental tools to predict and evaluate the extent to which abiotic stresses damage photosynthesis.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Abiotic stress; Chlorophyll a fluorescence; climate change; Gas exchange; Oxidative stress; photosynthesis

QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

Changes in limiting resources determine spatio-temporal variability in tree–grass interactions - Gea-Izquierdo, G; Montero, G; Cañellas, I (Agroforestry Systems, 2009)
Changing biotic and abiotic stress mediate in plant–plant interactions resulting in positive to neutral or negative effects, and these effects can change with gradients of stress or through plant dynamics. Here we studied the variability in annual grass production and composition induced by gradients of intercepted light by trees in years of contrasting precipitation in Mediterranean holm oak open woodlands. Although trees reduce the light radiance received by the pasture community, the presence of trees generally had a positive effect on pasture production in average climatic years where soil fertility was low. However, the interaction changed with increasing abiotic water stress. In a dry year, the increase in fertility could not be utilized and the effect of the crown was neutral. The effect of shade turned out to be beneﬁcial for growth, contrary to the situation in an average climatic year. Light insolation was positive for legume biomass. There was high variability in functional components over the course of the growing period and from 1 year to another. Under low levels of other biotic stresses such as livestock grazing or root competition, the limiting factor among light, soil moisture or soil nutrients may determine whether facilitation or competition occurs.
Keywords: Abiotic stress; competition; Dehesa; Facilitation; Grass production; Mediterranean

Changes in limiting resources determine spatio-temporal variability in tree–grass interactions - Gea-Izquierdo, G.; Montero, G.; Cañellas, I. (Agroforestry Systems, 2009)
Changing biotic and abiotic stress mediate in plant–plant interactions resulting in positive to neutral or negative effects, and these effects can change with gradients of stress or through plant dynamics. Here we studied the variability in annual grass production and composition induced by gradients of intercepted light by trees in years of contrasting precipitation in Mediterranean holm oak open woodlands. Although trees reduce the light radiance received by the pasture community, the presence of trees generally had a positive effect on pasture production in average climatic years where soil fertility was low. However, the interaction changed with increasing abiotic water stress. In a dry year, the increase in fertility could not be utilized and the effect of the crown was neutral. The effect of shade turned out to be beneﬁcial for growth, contrary to the situation in an average climatic year. Light insolation was positive for legume biomass. There was high variability in functional components over the course of the growing period and from 1 year to another. Under low levels of other biotic stresses such as livestock grazing or root competition, the limiting factor among light, soil moisture or soil nutrients may determine whether facilitation or competition occurs.
Keywords: Abiotic stress; competition; Dehesa; Facilitation; Grass production; Mediterranean